ENGLISH SPEAKING ANXIETY: SOURCES, COPING MECHANISMS, AND TEACHER MANAGEMENT - Milan, Mylene C (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This undertaking determined the anxieties of students towards spoken English - its sources, coping mechanisms and teacher management. Being qualitative, audio-recorded interview was utilized to gather data. Participants were thirteen teachers and students of speech classes in a state university located in the northern region of the Philippines. Data elicited were transcribed in verbatim, confirmed by the participants, coded and categorized, and themed accordingly. Triangulation through video-recorded observation of the teachers and focus-group discussion of the students’ companions established stronger validity of the data. Findings confirmed teachers’ and students’ awareness of existence of English Speaking Anxiety (ESA). Both teacher and student participants concur that students’ ESA mainly manifests in difficulty reciting competent ideas using English, hesitance to speak due to grammar and diction inaccuracies, and being perturbed by attention from the class. Sources of ESA progress from strong influence of students’ first language at home, to limited use of English language at school, and personal conclusions that the language is impractical and unnecessary in their future professions. Students cope with the anxiety by either appreciating the language’s relevance and applying it in all levels of communication or remaining unconcerned. Teachers reduce ESA phenomenon within the classroom by demonstrating strict correction and guidance, encouragements, translations, and eliminated criticisms. Conclusions revolve on ASE serving both positive and negative influences to English speaking skills of students but contributing more debilitating effects; reduction of ESA through teachers’ provision of more English speaking opportunities, students’ initiative of personal training, introduction and practice of English at an earlier age, and the inevitability of ESA in the affective domain which encourages teachers to enforce psychological positivism.